2018
DOI: 10.1186/s12970-018-0221-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of hydroxytyrosol dose on the redox status of exercised rats: the role of hydroxytyrosol in exercise performance

Abstract: BackgroundHydroxytyrosol (HT) is a polyphenol found in olive oil that is known for its antioxidant effects. Here, we aimed to describe the effects of a low and high HT dose on the physical running capacity and redox state in both sedentary and exercised rats.MethodsMale Wistar rats were allocated into 6 groups: sedentary (SED; n = 10); SED consuming 20 mg/kg/d HT (SED20; n = 7); SED consuming 300 mg/kg/d HT (SED300; n = 7); exercised (EXE; n = 10); EXE consuming 20 mg/kg/d HT (EXE20; n = 10) and EXE consuming … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 41 publications
3
17
0
Order By: Relevance
“…In this regard, the main limitation of the present study is that we have not quantified SKM oxidative status. However, the redox reactions produced in living cells following polyphenol Boots et al, 2007). This pro-oxidant effect has been reported in exercised rats supplemented with 12 mg•kg•d of quercetin (Casuso et al, 2015).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In this regard, the main limitation of the present study is that we have not quantified SKM oxidative status. However, the redox reactions produced in living cells following polyphenol Boots et al, 2007). This pro-oxidant effect has been reported in exercised rats supplemented with 12 mg•kg•d of quercetin (Casuso et al, 2015).…”
Section: Discussionmentioning
confidence: 93%
“…Deleterious effects on exercise performance have been reported in rodents consuming 20 mg·kg·d (Al Fazazi et al, 2018), a dose with high antioxidant potential within SKM (Cao et al, 2014). Notably, here we used significant lower HT doses that are known to be able to rise plasma antioxidant capacity.…”
Section: Discussionmentioning
confidence: 99%
“…In this way, previous studies have demonstrated the cardioprotective effect of VOO enriched in bioactive compounds from the olive oil in animals [8] and humans [9,10]. In fact, recent studies have shown a strong ergogenic effect on physical activity and remodeling of more efficient mitochondrial super-complexes with lower reactive oxygen-derived species production at doses 20 mg/kg and 300 mg/kg [11,12].…”
Section: Introductionmentioning
confidence: 93%
“…17,20 LPS intoxicated group (septic model): mice in this group were injected intraperitoneally with a single dose of LPS (10 mg/ kg) to induce septic response according to a previous report. 21 HT 20 mg+LPS: mice in this group were gavaged with HT 20 mg/kg for 10 consecutive days according to an earlier studies, 20,22 then injected intraperitoneally with a single dose of LPS (10 mg/ kg). HT 40 mg+ LPS: mice in this group were gavaged with HT 40 mg/kg for 10 consecutive days, then injected intraperitoneally with a single dose of LPS (10 mg/ kg). …”
Section: Methodsmentioning
confidence: 99%
“…HT 20 mg+LPS: mice in this group were gavaged with HT 20 mg/kg for 10 consecutive days according to an earlier studies, 20,22 then injected intraperitoneally with a single dose of LPS (10 mg/ kg).…”
Section: Methodsmentioning
confidence: 99%